2011
DOI: 10.4028/www.scientific.net/msf.675-677.739
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Nd:YAG Laser Welded Invar 36 Alloy

Abstract: Invar 36 alloy is increasingly used as a structural material for manufacture of liquefied natural gas (LNG) transporters and storage tanks. However, the conventional arc welding of Invar 36 alloy has high susceptibility of hot-cracking. As a high-energy-beam welding process, laser welding could be effective for producing defect-free Invar 36 weld. In the present study, defect-free Invar 36 weld was successfully produced by Nd:YAG laser welding. The microstructure and mechanical properties of weld were also tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…HIPing closed the majority of pores but led to coarsening of α precipitates especially those at GBs. The difference in the effect of heat treatment and HIPing on α precipitate size is unlikely to be due to the difference in the temperatures used for heat treatments (830°C and 570°C) and HIPing (950°C) given that the γ→α transformation temperature is actually below 500°C [4]. Instead, it should be attributed to the difference in cooling rate after heat treatments and HIPing.…”
Section: Microstructural Developmentmentioning
confidence: 97%
See 1 more Smart Citation
“…HIPing closed the majority of pores but led to coarsening of α precipitates especially those at GBs. The difference in the effect of heat treatment and HIPing on α precipitate size is unlikely to be due to the difference in the temperatures used for heat treatments (830°C and 570°C) and HIPing (950°C) given that the γ→α transformation temperature is actually below 500°C [4]. Instead, it should be attributed to the difference in cooling rate after heat treatments and HIPing.…”
Section: Microstructural Developmentmentioning
confidence: 97%
“…Invar 36, Fe-36wt.%Ni alloy, is well known for its low coefficient of thermal expansion (CTE) below its Curie temperature (230°C) and excellent mechanical properties in cryogenic environment [1][2][3][4][5]. Due to these features, it has been widely used as highly reliable and high precision materials in components where high dimensional stability is required.…”
Section: Introductionmentioning
confidence: 99%
“…Invar 36 alloy, as a nickel-iron alloy with excellent cryogenic characteristics, has received wide attention in various fields, such as in LNG carriers, precision instruments and other fields [4][5][6][7]. Previous studies have demonstrated that Invar 36 alloy as an outer ring material for LNG bearings exhibits excellent tribological properties under extremely cryogenic and dry conditions.…”
Section: Introductionmentioning
confidence: 99%
“…As a special functional material, Invar36 alloy is especially attractive for electronics industry, LNG storage tanks, long-distance power transmission lines, the forming mold of composite material and other fields on account of its extremely low coefficient of thermal expansion (CTE) below Curie temperature [1][2][3] . It is well known that the deformation behaviors of metals in hot forming process, significantly affected by the deformation parameters including strain, strain rate and temperature, have an important influence on the dimensional accuracy and mechanical properties of final products.…”
Section: Introductionmentioning
confidence: 99%